Antiretroviral agents against human immunodeficiency virus: an overview of current drugs and new perspectives - Oliveira, Ingrid Barcelos de; Santos, Claudio Cesar Cirne; Paixão, Izabel Christina Nunes de Palmer; Barros, Caroline de Souza; Pinho, Rosa Teixeira (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Since its discovery in the 1980s, the human immunodeficiency virus (HIV) has been the target of many studies. Nowadays, estimates show that 36.7 million people are infected with HIV worldwide. In Brazil, HIV infection overcomes 840 thousand people. Globally, only 53% of the HIV infected people are under antiretroviral therapy. Significant advances in antiretroviral therapy have been made since the introduction of zidovudine in 1987. Objective: To advance the discoveries of the available antivirals demonstrating their functional specificities. Methods: We performed a systematic review with a bibliographic survey in the Index Medicus/MEDLINE and PubMed databases for periodical and indexed articles, from 2013 to 2018 that reported on antiretrovirals used or not in the clinical practice. Results: Currently, there are six classes of antiretroviral drugs: nucleoside reverse transcriptase inhibitors (NRTIs), non-nucleoside reverse transcriptase inhibitors (NNRTIs), protease inhibitors (PIs), fusion inhibitors (FIs), entry inhibitors (CCRIs), and HIV integrase strand transfer inhibitors (INIs or INSTIs). In summary, several antiretroviral agents under development make HIV entry, reverse transcription, integration, and maturation emerging drug become targets. Conclusion: A multifaceted approach to antiretroviral therapy, using combinations of inhibitors that target different steps of the viral life cycle, has the best potential for long-term control of HIV infection.